2021
DOI: 10.1108/ijpdlm-06-2019-0199
|View full text |Cite
|
Sign up to set email alerts
|

Developing and implementing contextualised S&OP designs – an enterprise architecture management approach

Abstract: PurposeThis paper provides a five-step Enterprise Architecture Management (EAM) approach to systematically guide the development and implementation of contextualised Sales and Operations Planning (S&OP) designs.Design/methodology/approachA case study is conducted at a European chemical manufacturer. The research applies the five-step approach, embracing the descriptive and prescriptive EAM functions combined with the lens of contingency theory.FindingsThe research findings demonstrate the suitability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 37 publications
(117 reference statements)
0
35
0
4
Order By: Relevance
“…The S&OP process is a cross-functional business process designed to help companies in synchronizing supply and demand, in aligning strategic planning with daily activities, and by reviewing performance measures, in promoting continuous improvement (Grimson and Pyke, 2007; Wagner et al. , 2014; Ambrose and Rutherford, 2016; Noroozi and Wikner, 2017; Kreuter et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The S&OP process is a cross-functional business process designed to help companies in synchronizing supply and demand, in aligning strategic planning with daily activities, and by reviewing performance measures, in promoting continuous improvement (Grimson and Pyke, 2007; Wagner et al. , 2014; Ambrose and Rutherford, 2016; Noroozi and Wikner, 2017; Kreuter et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…, 2021). Many studies have shown that after the S&OP process implementation, supply and demand should always be aligned, and therefore help in preventing or mitigating the famous “bullwhip effect” (Olhager and Selldin, 2007; Lapide, 2011; Tuomikangas and Kaipia, 2014; Mello, 2015; Kreuter et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations